2012
DOI: 10.1007/s10897-012-9509-7
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Second Language Usage on Genetic Counseling Training and Supervision

Abstract: We conducted an exploratory study of the experiences of genetic counselors who have either trained or supervised in a second language to assess the relevance of this issue to genetic counseling training and supervision. Two hundred-thirty NSGC members, CAGC members and genetic counseling students completed the online questionnaire. Many of the respondents reported that training and supervision differed when another language was involved. Supervisors reported difficulty in assessing students' counseling skills … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…The plurality of papers in the GC supervision field are surrounding some of these difficulties. These six papers included the following: compassion fatigue/burnout from being a supervisor (Allsbrook et al, ), boundary issues (Gu, McCarthy Veach, Eubanks, LeRoy, & Callanan, ), multiculturalism/competence (Kyung Lee, McCarthy Veach, & LeRoy, ), anxiety (MacFarlane, McCarthy Veach, Grier, Meister, & LeRoy, ), games (McIntosh, Dircks, Fitzpatrick, & Shuman, ), and language issues (Vanneste et al, ). Each of these papers explored difficult aspects of the GC supervisor/student relationship, but all either suggest increasing the supervision working alliance or working with the GC program to identify ways to leverage existing resources to provide supervision training.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The plurality of papers in the GC supervision field are surrounding some of these difficulties. These six papers included the following: compassion fatigue/burnout from being a supervisor (Allsbrook et al, ), boundary issues (Gu, McCarthy Veach, Eubanks, LeRoy, & Callanan, ), multiculturalism/competence (Kyung Lee, McCarthy Veach, & LeRoy, ), anxiety (MacFarlane, McCarthy Veach, Grier, Meister, & LeRoy, ), games (McIntosh, Dircks, Fitzpatrick, & Shuman, ), and language issues (Vanneste et al, ). Each of these papers explored difficult aspects of the GC supervisor/student relationship, but all either suggest increasing the supervision working alliance or working with the GC program to identify ways to leverage existing resources to provide supervision training.…”
Section: Resultsmentioning
confidence: 99%
“…Supervisors may not know background information, such as total number of cases that are usually seen per student during the program or remediation policies (Berg et al, ; Lindh et al, ). Not having this information could lead to barriers to becoming supervisors. Include information about and solutions to previously identified Difficulties in Supervision: Increase supervisors' confidence and provide resources to address compassion fatigue and trait anxiety, ways to recognize these and seek help (Allsbrook et al, ). Boundary issues and resolution (e.g., through an informed consent document; Gu et al, ). Include cultural competency in the rotation (e.g., drawing attention to when sessions are tailored to the cultural identity of the patient/family/student; Kyung Lee et al, ). Recognize student anxiety is normal, how to use the SWA to decrease anxiety, and how to provide useful feedback (MacFarlane et al, ). Define supervision and student “games,” examples from each side, and how to spot and stop a game from continuing (McIntosh et al, ). Raise awareness of the needs of multilingual GC students and possible issues GC students and supervisors might face when another language is involved in supervision and training (Vanneste et al, ). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They recommended implementing specific training in supervision to build confidence and enhance supervisory skills, thereby alleviating these types of negative interactions with student supervisees. Vanneste et al (2013) suggested supervisor training could support new initiatives to increase diversity in the field of genetic counseling. Specifically, supervision training focused on bilingual genetic counseling student skill development would be beneficial for both supervisors and students.…”
Section: Clinical Supervision In Genetic Counselingmentioning
confidence: 99%
“…Anxiety related to supervision has been called Ba given…which must be taken into consideration by supervisors^ (Borders et al 2006, p. 212) and described as normative in genetic counseling (e.g., McCarthy Veach et al 2003;Wherley et al 2015) as well as in related fields such as medicine (e.g., Hajek et al 2000;Jiang et al 2003;Sarikaya et al 2006) and mental health (e.g., Bernard and Goodyear 2009;Skovholt and Ronnestad 2003;Stoltenberg and Delworth 1987). Anxiety has been shown to affect genetic counseling supervision from both the supervisors' perspective (Lindh et al 2003) and the students' perspective (Hendrickson et al 2002); it has been linked to Bgames^played in supervision by supervisees and supervisors (McIntosh et al 2006); and it may increase when counseling in a second language (Vanneste et al 2013). As literature on supervision continues to grow and become more empirically-based (cf.…”
Section: Anxiety Among Genetic Counseling Students and Counselorsmentioning
confidence: 99%